Genetic Variation at Microsatellite Loci in Odorrana hosii (Boulenger, 1891) - Djong Hon Tjong; Anugrah Viona Agesi; Dewi Imelda Roesma (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
The true frog species, Odorrana hosii, found in West Sumatera Indonesia, has high morphological differentiation and also estimated has high genetic variation. A total of 35 O. hosii at a seven location have analyzed using DNA microsatellite markers. Genetic variation of five microsatellite loci provided the highest value of expected heterozygosity (He) for the population in Padang (He= 0.618), while the lowest was the population in Merapi (He= 0.427). There are genetic differences in moderate levels among populations of O. hosii in West Sumatra (FST= 0.108) with inbreeding intrapopulation value (FIS= -0.559), and high value of gene flow among the populations (Nm = 2.061). This study becomes the first molecular data for establishing effective population management conservation.